2014
DOI: 10.1002/2013pa002581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of productivity, glaciation, and ventilation on late Quaternary sedimentary redox and trace element accumulation on the Vancouver Island margin, western Canada

Abstract: Variations in chalcophile and redox-sensitive trace elements are examined at high-resolution intervals from a~50 kyr long sediment core (MD02-2496) from the Vancouver Island margin. Enrichments of Ag, Cd, Re, U, and Mo above lithogenous levels, signifying sedimentary suboxia and anoxia, occurred during the early Holocene and Bølling/Allerød, and during warm interstadial events of Marine Isotope Stage (MIS) 3. Down-core trace element profiles co-vary with productivity proxy records (opal, CaCO 3 , and marine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 111 publications
(167 reference statements)
6
26
1
Order By: Relevance
“…S4 and S5). North of our study area, mass accumulation rates of marine organic carbon are controlled primarily by sedimention rates (especially in late glacial time), but also rise during interglacial time when sedimentation rates were lower (30). It is possible that organic carbon-based estimates of export productivity may work in some regions when confounding influences of preservation are relatively small.…”
Section: Resultsmentioning
confidence: 99%
“…S4 and S5). North of our study area, mass accumulation rates of marine organic carbon are controlled primarily by sedimention rates (especially in late glacial time), but also rise during interglacial time when sedimentation rates were lower (30). It is possible that organic carbon-based estimates of export productivity may work in some regions when confounding influences of preservation are relatively small.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in dissolved oxygen in O-LGM was considerable but agreed well with proxy reconstructions for the upper ocean. The oxygen-poor intermediate waters of the western North Pacific (Ishizaki et al, 2009;Shibahara et al, 2007), eastern North Pacific (Cannariato and Kennett, 1999;Cartapanis et al, 2011;Chang et al, 2014;Dean, 2007;Nameroff et al, 2004;Pride et al, 1999;Ohkushi et al, 2013;van Geen et al, 2003), eastern South Pacific (Martinez et al, 2006;Muratli et al, 2010;Salvatteci et al, 2016), equatorial Pacific (Leduc et al, 2010) and Indian Ocean (Reichart et al, 1998;Suthhof et al, 2001;van der Weijden et al, 2006) were better oxygenated at the LGM relative to the PI climate. An important consequence of oxygenating the upper ocean is a reduction in the strength of denitrification in these regions.…”
Section: Dissolved Oxygenmentioning
confidence: 95%
“…The net decline in export production observed in this study was dominated by the decline in tropical and subtropical waters. Many palaeoproductivity studies located outside of the subantarctic zone have found weakened productivity at the LGM (Chang et al, 2014(Chang et al, , 2015Costa et al, 2016;Crusius et al, 2004;Kohfeld et al, 2005;Kohfeld and Chase, 2011;Jaccard et al, 2005;McKay et al, 2015;Ortiz et al, 2004;Riethdorf et al, 2013;Salvatteci et al, 2016;Singh et al, 2011;Thomas et al, 1995). Additionally, an enhanced utilisation of available nutrients in the subantarctic zone would reduce the nutrient content of intermediate waters formed in the Southern Ocean and would thus reduce the delivery of nutrients to lower latitudes (Sarmiento et al, 2004).…”
Section: Reconciling Export Productionmentioning
confidence: 99%
“…Sources, depositional and postdepositional processes are reconstructed by using suites of major and trace element proxies (e.g., Tribovillard et al, 2006;Calvert and Pedersen, 2007;Chang et al, 2014;Riedinger et al, 2014). In particular, paleoclimate and paleoceanographic reconstructions have been based on geochemical proxies, because climate changes often cause significant variations in the composition of marine sediments, influenced by terrigenous input, paleocirculation, and depositional redox conditions.…”
Section: Elemental Ratios As Paleoclimate and Paleoceanographic Proximentioning
confidence: 99%